2021
DOI: 10.1177/17479541211046910
|View full text |Cite
|
Sign up to set email alerts
|

Differences in expertise level for anticipatory skill between badminton ‘in game’ strokes and serves

Abstract: Over the past decades, researchers in racquet sports have been testing the role of visual anticipation and expert attunement to essential kinematic information for responding to ‘in game’ strokes as well as serves. However, anticipatory behaviour to both strokes has not been compared directly, in spite of the different characteristics of these strokes in the context of badminton. Therefore, this study explored the differences in anticipatory behaviour among elite ( n = 26), competitive ( n = 15) and novices ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In particular, temporal occlusion has been used to study the quality and the accuracy of decisions made by athletes and, likewise, to examine how these aspects are influenced by various covariates, such as age, the relative age effect, or competence, as well as acute factors such as fatigue [3]. Comparisons between experienced and non-experienced players have shown that the experts' superior skills allow them to make accurate decisions faster than their non-experienced counterparts [23][24][25][26]. The higher performance of expert athletes depends primarily on the internal mental representations and cognitive processes that mediate the interpretation of a stimulus and the selection of an appropriate response [3].…”
Section: Methodological Approaches In Decision-making Researchmentioning
confidence: 99%
“…In particular, temporal occlusion has been used to study the quality and the accuracy of decisions made by athletes and, likewise, to examine how these aspects are influenced by various covariates, such as age, the relative age effect, or competence, as well as acute factors such as fatigue [3]. Comparisons between experienced and non-experienced players have shown that the experts' superior skills allow them to make accurate decisions faster than their non-experienced counterparts [23][24][25][26]. The higher performance of expert athletes depends primarily on the internal mental representations and cognitive processes that mediate the interpretation of a stimulus and the selection of an appropriate response [3].…”
Section: Methodological Approaches In Decision-making Researchmentioning
confidence: 99%